Submicron ceramic slurry, high-compactness ceramic diaphragm and preparation method of high-compactness ceramic diaphragm
Through a specific ball milling process, including two-stage ball milling and the use of an appropriate amount of adhesive, a submicron-scale ceramic slurry is prepared, which solves the problem that the ceramic particle size value and density are difficult to meet the needs of MLCC miniaturization and high capacity, and realizes the problem of the need for small-scale and high-capacity of ceramic particles. The ceramic diaphragm has a higher density and smoothness.
Patent Information
- Application Number
- CN202411347936.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-18
AI Technical Summary
The existing ball milling process is difficult to meet the needs of MLCC miniaturization and high capacity development, especially in terms of ceramic particle size and density.
Submicron-scale ceramic slurry is prepared by mixing zirconia balls with ceramic powder, organic solvents, dispersants, and defoaming agents at a specific mass ratio, and performing two-stage ball milling at a specific rotation speed and time. The method includes a definition of the ball milling time in the first stage and a ball milling after the adhesive is added in the second stage.
The smaller particle size value and more concentrated particle size distribution of ceramic slurry are achieved, thereby improving the density and flatness of the ceramic diaphragm, supporting the miniaturization and high capacity development of MLCC.
Smart Images

Figure CN119462077A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic materials, and in particular to a submicron ceramic slurry, a high-density ceramic diaphragm and a preparation method thereof. Background Art
[0002] With the rapid development of the world's electronics industry, as a basic component of the electronics industry, chip capacitors (MLCC) are also developing at an astonishing speed, increasing at a rate of 10% to 15% per year. At present, the global demand for chip capacitors is about 200 billion. In order to meet the continuous development of electronic equipment towards miniaturization, large capacity, high reliability and low cost, MLCC is also developing rapidly, with increasing types, shrinking volumes, improving performance, advancing technology, and updating materials. Light, thin, short and small series products have tended to be standardized and universal, which also puts forward new requirements for the preparation process of MLCC diaphragms.
[0003] As MLCC continues to develop in miniaturization and high capacity, the ceramic film medium is required to have a thinner thickness and better density, which requires the ceramic slurry to have a smaller particle size and a more concentrated particle size distribution. For sub-micron ceramic powder, the current ball milling process conditions cannot further reduce the particle size of ceramic particles, ensure dispersion and density, and cannot well meet the development needs of MLCC miniaturization and high capacity. Summary of the invention
[0004] The purpose of the present invention is to provide a submicron ceramic slurry, a high-density ceramic diaphragm and a preparation method thereof, which solves the problem that the existing ball milling process conditions are difficult to meet the development needs of MLCC miniaturization and high capacity.
[0005] The present invention is achieved through the following technical solutions:
[0006] In one aspect, the present invention provides a method for preparing a submicron ceramic slurry, comprising the following steps:
[0007] Zirconia balls with a diameter of 1 to 6 mm are mixed with ceramic powder, organic solvent, dispersant and defoamer in a mass ratio of 6:1:(0.2 to 0.4):(0.01 to 0.02):0.002, and the first stage of ball milling is carried out at a rotation speed of 50 r / min-60 r / min for 3 to 30 h;
[0008] After the first stage of ball milling is completed, a binder is added to the mixed slurry for the second stage of ball milling to obtain a submicron ceramic slurry with high fluidity.
[0009] Furthermore, in the method for preparing the submicron ceramic slurry, the organic solvent is prepared from toluene and ethanol.
[0010] Furthermore, in the method for preparing the submicron ceramic slurry, the mass ratio of toluene to ethanol in the organic solvent is (5-6): 3.5.
[0011] Furthermore, in the method for preparing the submicron ceramic slurry, the adhesive is prepared by mixing toluene, ethanol, plasticizer and resin in a mass ratio of 3.5:0.8:1.7:1.
[0012] Furthermore, in the method for preparing the submicron ceramic slurry, the diameter of the zirconia ball is 2 mm.
[0013] Furthermore, in the method for preparing the submicron ceramic slurry, the ball milling time in the first stage is 24 hours.
[0014] Furthermore, in the method for preparing the submicron ceramic slurry, the conditions for the second stage of ball milling are: a rotation speed of 50 r / min-60 r / min, and a ball milling time of 24 to 30 hours.
[0015] In a second aspect, the present invention provides a submicron ceramic slurry, wherein the submicron ceramic slurry is prepared by the above-mentioned method for preparing the submicron ceramic slurry.
[0016] In a third aspect, the present invention provides a method for preparing a high-density ceramic diaphragm, comprising the following steps:
[0017] The submicron ceramic slurry is cast at a temperature not lower than 70° C. to form a high-density ceramic diaphragm.
[0018] In a fourth aspect, the present invention provides a high-density ceramic diaphragm, wherein the ceramic diaphragm is prepared by the above-mentioned method for preparing the high-density ceramic diaphragm.
[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0020] The preparation method of submicron ceramic slurry provided by the present invention limits the zirconia balls of different sizes and the ball milling time of the first stage, and uses a laser particle size analyzer to obtain the ball milling size conditions after the first stage ball milling is completed and the particle size value and particle size distribution under the ball milling time of the first stage. The results show that the grinding effect is obvious, and the ceramic slurry finally obtained has smaller particle size values (D10, D50, D90) and a more concentrated particle size distribution.
[0021] The preparation method of the high-density ceramic diaphragm provided by the present invention is to obtain a submicron ceramic slurry with a smaller particle size value (D10, D50, D90) and a more concentrated particle size distribution by slit casting using a casting machine to obtain a corresponding ceramic diaphragm. The ceramic diaphragm exhibits better density and flatness, the pores between particles are significantly reduced, and the agglomeration is greatly improved, which further improves the density of the ceramic diaphragm and provides strong support for the miniaturization and high capacity of subsequent products. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0023] Figure 1 The particle size of the mixed slurry after different ball milling times in the first stage in Experimental Example 1 of the present invention with 1 mm diameter zirconium oxide balls;
[0024] Figure 2 The particle size of the mixed slurry after different ball milling times in the first stage in Experimental Example 1 of the present invention with 2 mm diameter zirconium oxide balls;
[0025] Figure 3 The particle size of the mixed slurry after different ball milling times in the first stage in Experimental Example 1 of the present invention with 3 mm diameter zirconium oxide balls;
[0026] Figure 4 The particle size of the mixed slurry after different ball milling times in the first stage in Experimental Example 1 of the present invention with a diameter of 4 mm zirconium oxide balls;
[0027] Figure 5 The particle size of the mixed slurry after different ball milling times in the first stage in Experimental Example 1 of the present invention with 6 mm diameter zirconium oxide balls;
[0028] Figure 6 The particle size value of the mixed slurry of zirconia balls with different diameters after ball milling for 24 hours in the first stage in Experimental Example 2 of the present invention;
[0029] Figure 7 This is the microscopic characterization of each ceramic diaphragm in Experimental Example 3 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0031] At present, ball mill is the most widely used equipment in the field of electronic ceramics and can fully grind and disperse ceramic powder. Use an appropriate number of grinding balls, add corresponding solvents and additives, and mix them in the ball mill for a certain period of time to obtain a ceramic slurry with uniform dispersion and good density. The process parameters of ball milling have an extremely important influence on the ball milling effect of ceramic slurry.
[0032] The present invention provides a method for preparing a submicron ceramic slurry, comprising:
[0033] Zirconia balls with a diameter of 1 to 6 mm are mixed with ceramic powder, organic solvent, dispersant and defoamer in a mass ratio of 6:1:(0.2 to 0.4):(0.01 to 0.02):0.002, and the first stage of ball milling is carried out at a rotation speed of 50 r / min-60 r / min for 3 to 30 h;
[0034] After the first stage of ball milling is completed, a binder is added to the mixed slurry for the second stage of ball milling to obtain a submicron ceramic slurry with high fluidity.
[0035] The preparation method of submicron ceramic slurry provided by the present invention limits the zirconia balls of different sizes and the ball milling time of the first stage, and uses a laser particle size analyzer to obtain the ball milling size conditions after the first stage ball milling is completed and the particle size value and particle size distribution under the ball milling time of the first stage. The results show that the grinding effect is obvious, and the ceramic slurry finally obtained has smaller particle size values (D10, D50, D90) and a more concentrated particle size distribution.
[0036] In the present invention, the diameter of the zirconia ball can be 1mm, 2mm, 3mm, 4mm or 6mm, etc., but is not limited to the listed values, and other values not listed in the range are also applicable. Selecting a small-sized zirconia ball has a larger specific surface area, which can provide more effective grinding contact points during the grinding process, and more effectively accelerate the ceramic grinding process in the same time. In addition, due to its small size, the zirconia ball is easier to fully disperse in the grinding medium, ensuring that it can be fully affected by the grinding medium during the grinding process. Compared with larger-sized grinding media, small-sized zirconia balls usually produce less wear because the collision energy between them is smaller, which can extend the service life of the grinding medium and reduce the loss cost during the grinding process. Small-sized zirconia balls can provide a finer grinding effect, making the final ceramic slurry particle size more uniform and delicate and more suitable for electronic materials.
[0037] In the present invention, the grinding time of the first stage can be 3h, 5h, 7h, 9h, 11h, 24h, 30h, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable. The grinding effect is also affected by the grinding time. The length of the grinding time will significantly affect the particle size and uniformity of the final product: if the grinding time is too short, the contact time between the zirconia ball and the ceramic is too short, and the ceramic is not fully ground; the longer the grinding time, the more sufficient the contact time between the zirconia ball and the ceramic material, which can make the particles finer and more uniform. In the present invention, appropriately extending the grinding time can help to better remove the roughness and unevenness of the ceramic surface, thereby improving the surface quality and smoothness of the ceramic slurry, and laying the foundation for the high density of the later ceramic diaphragm. However, the grinding time should not be too long, and excessive grinding time may cause excessive wear of the zirconia ball. Therefore, the present invention limits the grinding time of the first stage to a suitable range of 3 to 30h.
[0038] In some feasible embodiments, the organic solvent is prepared from toluene and ethanol.
[0039] In some feasible embodiments, the mass ratio of toluene to ethanol in the organic solvent is (5-6): 3.5.
[0040] In some feasible embodiments, the adhesive is prepared by mixing toluene, ethanol, plasticizer, and resin in a mass ratio of 3.5:0.8:1.7:1.
[0041] Preferably, the mass ratio of the above-mentioned adhesive to the ceramic powder is 1:(2.5-3); the plasticizer is DBP plasticizer (dibutyl phthalate); and the resin is PVB resin (polyvinyl butyral resin).
[0042] In some feasible embodiments, the zirconia ball has a diameter of 2 mm.
[0043] In some feasible embodiments, the first stage ball milling time is 24 hours.
[0044] In some feasible methods, the conditions for the second stage of ball milling are: rotation speed 50r / min-60r / min, and ball milling time 24 to 30h.
[0045] The present invention provides a method for preparing a high-density ceramic diaphragm, comprising: casting the above-mentioned submicron ceramic slurry at a temperature not lower than 70° C. to form a high-density ceramic diaphragm.
[0046] The preparation method of the high-density ceramic diaphragm provided by the present invention is to obtain a submicron ceramic slurry with a smaller particle size value (D10, D50, D90) and a more concentrated particle size distribution by slit casting using a casting machine to obtain a corresponding ceramic diaphragm. The ceramic diaphragm exhibits better density and flatness, the pores between particles are significantly reduced, and the agglomeration is greatly improved, which further improves the density of the ceramic diaphragm and provides strong support for the miniaturization and high capacity of subsequent products.
[0047] In the present invention, the casting temperature can be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0048] In order to further illustrate the present invention, a submicron ceramic slurry, a highly densified ceramic diaphragm and a preparation method thereof provided by the present invention are described below in combination with embodiments. However, it should be understood that these embodiments are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating procedures are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following embodiments.
[0049] Example 1
[0050] The method for preparing the submicron ceramic slurry provided in this embodiment comprises the following steps:
[0051] (1) Before using the ceramic powder, dry it to control the moisture content and avoid the introduction of impurities. Then weigh the cleaned zirconia balls, add the zirconia balls with a diameter of 1 mm into the ball mill and add the dried ceramic powder in time to prevent the ceramic powder from absorbing moisture again.
[0052] (2) Continue to add the dispersant and the defoamer to step (1), and then add the organic solvent. Further, the organic solvent includes toluene and ethanol in a mass ratio of 5:3.5.
[0053] Among them, the mass ratio of zirconia balls to ceramic powder, organic solvent, dispersant and defoaming agent is 6:1:0.2:0.01:0.002.
[0054] (3) After completing step (2), the first stage of ball milling was carried out in a sealed ball mill jar, the ball mill speed was controlled at 50 r / min-60 r / min, and the ball milling time was 3 h.
[0055] (4) Based on the mixed slurry obtained in step (3), a Malvern laser particle size analyzer is used to obtain a particle size value and a particle size distribution of the mixed slurry.
[0056] (5) After completing step (4), open the ball mill and add an appropriate amount of adhesive (the mass ratio of adhesive to ceramic powder is 1:2.5), seal the ball mill and carry out the second stage of ball milling. The ball mill speed is controlled at 50-60 r / min and the ball milling time is 3 h.
[0057] The adhesive is prepared by mixing toluene, ethanol, plasticizer and resin in a mass ratio of 3.5:0.8:1.7:1.
[0058] Test Example 1:
[0059] Referring to the preparation method of Example 1, the ball milling time of step (3) in Example 1 was set to 3h, 5h, 7h, 9h, 11h, 24h and 30h respectively in this test example, and the diameter of the zirconia ball was set to 1mm, 2mm, 3mm, 4mm and 5mm respectively. After the first stage was completed, the particle size value and particle size distribution of each grinding time condition under different zirconia ball milling size conditions were obtained by using a laser particle size analyzer for the mixed slurry. The results are shown in Figure 1-5 shown.
[0060] As can be seen from the figure, with the increase of the first stage ball milling time, the overall particle size of the mixed slurry shows a trend of first decreasing and then increasing. The particle size reaches the minimum value after 24 hours of ball milling. After continuing ball milling for 30 hours, the particle size value of the mixed slurry begins to increase. The results show that the extension of ball milling time can achieve the purpose of refining particles with smaller particle size to a certain extent, but the ball milling time cannot be increased blindly. Too long ball milling will increase the particle size. The best first stage ball milling time in this test example 1 should be 24 hours.
[0061] Test Example 2:
[0062] Referring to the preparation method of Example 1, the first stage of the ball milling time of step (3) in Example 1 was set to 24h in this test example, and the diameters of the zirconia balls were set to 1mm, 2mm, 3mm, 4mm, and 5mm, respectively. After the first stage was completed, the mixed slurry was subjected to a laser particle size analyzer to obtain the particle size values and particle size distribution of different zirconia ball milling size conditions under the grinding time of 24h. The results are shown in FIG. Figure 6 shown.
[0063] from Figure 6 It can be seen that as the diameter of the zirconium oxide ball decreases, the overall particle size of the mixed slurry shows a decreasing trend, and the smaller the diameter of the zirconium oxide ball, the smaller the particle size fluctuation. After ball milling with a 1mm zirconium oxide ball, the slurry completely adheres to the surface of the zirconium oxide ball, making it impossible to pour the material, and the viscosity value exceeds the viscosity meter range, so the slurry is not continued to be used. The results show that the reduction in the size of the zirconium oxide ball can better refine the particle size of the ceramic slurry. However, too small a zirconium oxide ball will cause the viscosity of the mixed slurry after ball milling to be too large and cannot be used. The optimal diameter of the zirconium oxide ball in this embodiment is 2mm.
[0064] Example 2
[0065] The method for preparing the submicron ceramic slurry provided in this embodiment comprises the following steps:
[0066] (1) Before using the ceramic powder, dry it to control the moisture content and avoid the introduction of impurities. Then weigh the cleaned zirconia balls, add the zirconia balls with a diameter of 4 mm into the ball mill and add the dried ceramic powder in time to prevent the ceramic powder from absorbing moisture again.
[0067] (2) Continue to add the dispersant and the defoaming agent to step (1), and then add the organic solvent, further, the organic solvent includes toluene and ethanol, and the mass ratio is 5.5:3.5.
[0068] Among them, the mass ratio of zirconia balls to ceramic powder, organic solvent, dispersant and defoaming agent is 6:1:0.3:0.01:0.002.
[0069] (3) After completing step (2), the first stage of ball milling was carried out in a sealed ball mill jar, the ball mill speed was controlled at 50 r / min-60 r / min, and the ball milling time was 9 h.
[0070] (4) Based on the mixed slurry obtained in step (3), a Malvern laser particle size analyzer is used to obtain a particle size value and a particle size distribution of the mixed slurry.
[0071] (5) After completing step (4), open the ball mill and add an appropriate amount of adhesive (the mass ratio of adhesive to ceramic powder is 1:2.8), seal the ball mill and carry out the second stage of ball milling. The ball mill speed is controlled at 50-60 r / min and the ball milling time is 9 h.
[0072] The adhesive is prepared by mixing toluene, ethanol, plasticizer and resin in a mass ratio of 3.5:0.8:1.7:1.
[0073] Example 3
[0074] The method for preparing the submicron ceramic slurry provided in this embodiment comprises the following steps:
[0075] (1) Before using the ceramic powder, dry it to control the moisture content and avoid the introduction of impurities. Then weigh the cleaned zirconia balls, add the zirconia balls with a diameter of 2 mm into the ball mill and add the dried ceramic powder in time to prevent the ceramic powder from absorbing moisture again.
[0076] (2) Continue to add the dispersant and the defoaming agent to step (1), and then add the organic solvent, further, the organic solvent includes toluene and ethanol, and the mass ratio is 6:3.5.
[0077] Among them, the mass ratio of zirconia balls to ceramic powder, organic solvent, dispersant and defoaming agent is 6:1:0.4:0.02:0.002.
[0078] (3) After completing step (2), the first stage of ball milling is carried out in a sealed ball mill jar, the ball mill speed is controlled at 50 r / min-60 r / min, and the ball milling time is 24 h.
[0079] (4) Based on the mixed slurry obtained in step (3), a Malvern laser particle size analyzer is used to obtain a particle size value and a particle size distribution of the mixed slurry.
[0080] (5) After completing step (4), open the ball mill and add an appropriate amount of adhesive (the mass ratio of adhesive to ceramic powder is 1:3), seal the ball mill and carry out the second stage of ball milling. The ball mill speed is controlled at 50-60 r / min and the ball milling time is 24 h.
[0081] The adhesive is prepared by mixing toluene, ethanol, plasticizer and resin in a mass ratio of 3.5:0.8:1.7:1.
[0082] Example 4
[0083] The method for preparing a highly densified ceramic diaphragm provided in an embodiment of the present invention comprises the following steps:
[0084] Based on the ceramic slurry obtained in step (5) of Example 1, a tape casting machine was used for tape casting. Furthermore, the tape casting was performed under the condition that the drying temperature of the tape casting machine was 65°C.
[0085] The ceramic diaphragm obtained in this embodiment is observed for appearance using a film selection table. After passing the inspection, the thickness of the ceramic diaphragm is tested using a thickness gauge, and a density test is performed.
[0086] The density test method is: use a thickness gauge to test the thickness of the ceramic film, then use a 13cm×13cm square mold to cut and calculate the volume of the ceramic film, and weigh it, and use the density calculation formula to get the density value of the ceramic film.
[0087] Based on the qualified ceramic diaphragms obtained, their density was calculated and the compact state of the ceramic diaphragms was observed under a scanning electron microscope.
[0088] Test Example 3:
[0089] The diameter of the zirconia ball in step (1) of Example 3 is set to 2 mm, and the ball milling time in step (3) is set to 11 h, 24 h and 30 h respectively. Ceramic slurry is prepared according to the preparation method of Example 3, and then the ceramic slurry is prepared into a ceramic diaphragm according to the method of Example 4. The ceramic diaphragm prepared by the existing process is used as a control for macroscopic and microscopic characterization, wherein the existing process is ball milling with 3 mm zirconia balls for 5 h.
[0090] The macroscopic characterization was compared from three aspects: defect quantity, diaphragm thickness and diaphragm density. The results are shown in Table 1.
[0091] Table 1 Appearance, thickness and density of ceramic diaphragm
[0092] Process conditions Number of ceramic film defects / piece Average thickness / μm <![CDATA[Density / g / cm 3 > Normal process 0 15.10 3.2017 2mm+ball milling 11h 0 15.04 3.4122 2mm+ball milling 24h 0 15.01 3.5190 2mm+ball milling 30h 0 14.91 3.4189
[0093] The results in Table 1 show that compared with the existing process, after 2mm diameter zirconia ball milling for 24 hours, the final ceramic diaphragm exhibits better density and flatness, the pores between particles are significantly reduced, and the agglomeration is greatly improved, further improving the density of the ceramic diaphragm.
[0094] Microscopic characterization Scanning electron microscopy was used to determine the microscopic density of the ceramic membrane and the microscopic morphology of the ceramic membrane was characterized at a magnification of 10 μm. The results are shown in Figure 7 shown.
[0095] Figure 7 The results show that compared with the existing process, after 24 hours of ball milling with 2mm zirconium balls, the ceramic diaphragm exhibits better density and flatness, the pores between particles are significantly reduced, and the agglomeration is greatly improved, further improving the density of the ceramic diaphragm.
[0096] Through the above macroscopic and microscopic characterization results, it is clear that using 2mm zirconia balls and controlling the first-stage ball milling time to 24h can effectively reduce the porosity of the ceramic diaphragm, increase the density of the ceramic diaphragm, and improve the agglomeration phenomenon, providing strong support for the miniaturization and high capacity of subsequent products.
[0097] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a submicron ceramic slurry, characterized in that: The following steps are involved: Zirconia balls with a diameter of 1 to 6 mm are mixed with ceramic powder, organic solvent, dispersant and defoamer in a mass ratio of 6:1:(0.2 to 0.4):(0.01 to 0.02):0.002, and the first stage of ball milling is carried out at a rotation speed of 50 r / min-60 r / min for 3 to 30 h; After the first stage of ball milling is completed, a binder is added to the mixed slurry for the second stage of ball milling to obtain a submicron ceramic slurry with high fluidity.
2. The method for preparing submicron ceramic slurry according to claim 1, characterized in that: The organic solvent is prepared from toluene and ethanol.
3. The method for preparing submicron ceramic slurry according to claim 2, characterized in that: The mass ratio of toluene to ethanol in the organic solvent (5-6) is 3.
5.
4. The method for preparing submicron ceramic slurry according to claim 1, characterized in that: The adhesive is prepared by mixing toluene, ethanol, plasticizer and resin in a mass ratio of 3.5:0.8:1.7:
1.
5. The method for preparing submicron ceramic slurry according to claim 1, characterized in that: The diameter of the zirconia ball is 2 mm.
6. The method for preparing submicron ceramic slurry according to claim 5, characterized in that: The first stage ball milling time is 24h.
7. The method for preparing submicron ceramic slurry according to claim 1, characterized in that: The conditions for the second stage of ball milling are: rotation speed 50r / min-60r / min, ball milling time 24 to 30h.
8. A submicron ceramic slurry, characterized in that: The submicron ceramic slurry is prepared by the method for preparing the submicron ceramic slurry according to any one of claims 1 to 7.
9. A method for preparing a high-density ceramic diaphragm, characterized in that: The following steps are involved: The submicron ceramic slurry described in claim 8 is cast at a temperature not lower than 70° C. to form a high-density ceramic diaphragm.
10. A high-density ceramic diaphragm, characterized in that: The ceramic diaphragm is prepared by the preparation method of the high-density ceramic diaphragm according to claim 9.